An investigation concerning a water soluble component extracted from the mature seed of Lotus pedunculatus (family: Leguminosae) : a thesis presented in partial fulfillment of the requirements for the degree of Master of Agricultural Science in Plant Biochemistry, Massey University of Manawatu, New Zealand - Beveridge, Robert John (Massey University, 1965)
1.1 GENERAL SURVEY OF THE FIELD OF PLANT GUMS AND MUCILAGES Smith and Montgomery (1) state in the preface to their monograph that plant gums and mucilages have been known and in use since very early times. References can be found to them in the Bible and they seem to have had commercial value for several 1000 years, especially for India, Asia, Africa, Australia and China. These products found a market in Europe where their use in industry has never ceased to expand. Seaweed gums have been used by the natives of the coastal regions of France, Wales, Ireland, Scotland and Scandinavia in food and medicinal preparations. (1) Plant gums are defined by Jones, J.K.N. and Smith, F (2) as substances of plant origin, which are obtained as exudations from fruit, trunks or branches of trees, spontaneously or after invasion by bacteria or fungi. When exposed to air and allowed to dry they form clean, glassy masses, usually coloured from dark brown to clear yellow. The quantity of gum excreted is a function of (a) the species of plant, (b) the environmental conditions and state of health in which the species is found (1). Their most probable function appears to be directly concerned with the sealing off of injured parts and thus preventing the loss of moisture. This property would also serve to prevent the invasion of the tissue by bacteria and fungi (1,2). Of the several theories (1) that exist to explain the biochemical origin of gums, the most probable is that they are a product of normal plant metabolism. Other workers have suggested that they are a product of pathological conditions induced by the infection of the plant by micro-organisms (1). Whether or not gums are formed at the site of injury or synthesised elsewhere in the plant and then transported to the injured area has yet to be ascertained. Chemical structural work has shown that there is a striking similarity among plant gums isolated from the same plant species (2). This would seem to indicate that the structural pattern is under genetical control via protein enzymes. [FROM INTRODUCTION]
Keywords: Plants -- Analysis; Polysaccharides; Lotus pedunculatus -- Seeds